ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PEMBELIAN IMPULSIF PADA KONSUMEN BUTIK 79 DI PALEMBANG TRADE CENTER PALEMBANG - Dewi Permata Sari; Ahmad Widad; Dian Eka (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2014)
This research is aimed to determine the influence of shopping lifestyle, fashion involvement, pre-decision stage, and post-decision stage toward impulse buying simultantly or partially. The target population in this research is the customer of Butik 79 in Palembang Trade Center Mall Palembang. There are 100 respondents of the sample in this research. Sampling technique used was non probability sampling. The analysis technique for this research was multiple regression analysis. The result of the simultaneous analysis indicates that shopping lifestyle, fashion involvement, pre-decision stage, and post-decision stage variables have significant influence toward impulse buying. Partially, shopping lifestyle and fashion involvement have positive influence, but not too significant toward impulse buying, while pre-decision stage and post-decision stage have positive and significant effect toward impulse buying.Keywords : Shopping lifestyle, fashion involvement, pre-decision stage, post-decision stage, and impulse buying.